The pathogenic biomarker alcohol dehydrogenase protein is involved in Bacillus cereus virulence and survival against host innate defence. - Devon W Kavanaugh; Constance Porrini; Rozenn Dervyn; Nalini Ramarao (PLoS ONE)
Bacillus cereus is a spore forming bacteria recognized among the leading agents responsible for foodborne outbreaks in Europe. B. cereus is also gaining notoriety as an opportunistic human pathogen inducing local and systemic infections. The real incidence of such infection is likely underestimated and information on genetic and phenotypic characteristics of the incriminated strains is generally scarce. We have recently analyzed a large strain collection of varying pathogenic potential. Screening for biomarkers to differentiate among clinical and non-clinical strains, a gene encoding an alcohol dehydrogenase-like protein was identified among the leading candidates. This family of proteins has been demonstrated to be involved in the virulence of several bacterial species. The relevant gene was knocked out to elucidate its function with regards to resistance to host innate immune response, both in vitro and in vivo. Our results demonstrate that the adhB gene plays a significant role in resistance to nitric oxide and oxidative stress in vitro, as well as its pathogenic ability with regards to in vivo toxicity. These properties may explain the pathogenic potential of strains carrying this newly identified virulence factor.